2019
DOI: 10.1055/a-0970-9104
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Bimodal and Unimodal Force-time Curves During Countermovement Jump

Abstract: This study aimed to explore the biomechanical differences between single and double peak ground reaction force-time curves during the countermovement jump with respect to kinematics, kinetics, and coordination of the lower extremities. Twenty-five college students were stratified into a single peak curve group and a double peak curve group. Eight infrared cameras and two force platforms were synchronized to collect the data. Independent t-tests were performed with groups for each dependent kinematic, kinetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 44 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…What differed among these methods was how the low-pass cutoff frequency was determined for each trial. For the 50-Hz method, a cutoff frequency of 50 Hz was selected because of its widespread use in CMVJ studies (2,4,16,18,38). The visual inspection 1 method determined the cutoff frequency based on a subjective visual analysis of the signal frequency content.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…What differed among these methods was how the low-pass cutoff frequency was determined for each trial. For the 50-Hz method, a cutoff frequency of 50 Hz was selected because of its widespread use in CMVJ studies (2,4,16,18,38). The visual inspection 1 method determined the cutoff frequency based on a subjective visual analysis of the signal frequency content.…”
Section: Methodsmentioning
confidence: 99%
“…Still, numerous CMVJ studies have analyzed raw GRF data or failed to indicate whether filtered or raw GRF data were analyzed (32,33,37,39,47) despite the possible influence of filtering on study results. In CMVJ studies using a low-pass filter, cutoff frequencies of 10 Hz (46), 12 Hz (24), 16 Hz (5), 17 Hz (30,34), 30 Hz (15), 40 Hz (44,45), and 50 Hz (2,16,18,38) have been reported. Some CMVJ studies provide justification for the selected cutoff frequency, such as plotting the frequency content of the recorded signals and subjectively estimating the primary frequency band (15,16), use of an objective determination method (34,45), or citing its use in a previous study (3,30).…”
Section: Introductionmentioning
confidence: 99%
“…The continuous concentric contraction and eccentric contraction of the muscles are called the stretch-shortening cycle (SSC) [2]. Past studies have found that using the SSC elastic energy mechanism increases the strength, speed, and muscle activation of the CMJ eccentric phase and increases the jump height during the CMJ concentric phase [3]. Thus, applying the SSC mechanism can enhance the muscle strength of the lower extremities and the jumping height in the CMJ to improve athletic perfor-mance.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, applying the SSC mechanism can enhance the muscle strength of the lower extremities and the jumping height in the CMJ to improve athletic perfor-mance. In addition, previous studies have found that drop jumps (DJs) are an effective plyometric training (PT) and SSC training method, currently being widely used to improve jumping ability and leg strength to improve athletic performance [3,4]. Therefore, DJ training can enhance the SSC mechanism to improve CMJ performance.…”
Section: Introductionmentioning
confidence: 99%
“…The countermovement jump (CMJ) is a dynamic plyometric training method for multijoint movement of the lower extremities, which rapidly develops strength through higher eccentric force to increase the concentric force development of the stretching-shortening cycle (SSC) mechanism [1]. The drop jump (DJ) is widely used to increase muscle strength and improve the SSC ability as an effective plyometric training method [2].…”
Section: Introductionmentioning
confidence: 99%